Comparative Evaluation of T-Cell Immune Response to BTV Infection in Sheep Vaccinated with Pentavalent BTV Vaccine When Compared to Un-Vaccinated Animals - Molalegne Bitew; Chintu Ravishankar; Soumendu Chakravarti; Gaurav Kumar Sharma; Sukdeb Nandi (Veterinary Medicine International)
Recent invasion of multiple bluetongue virus serotypes (BTV) in different regions of the world necessitates urgent development of efficient vaccine that is directed against multiple BTV serotypes. In this experimental study, cell mediated immune response and protective efficacy of binary ethylenimine (BEI) inactivated Montanide™ ISA 206 adjuvanted pentavalent (BTV-1, 2, 10, 16 and 23) vaccine was evaluated in sheep and direct challenge with homologous BTV serotypes in their respective group. Significant (P<0.05) up-regulation of mRNA transcripts of IFN-α, IL-2, IL-6, IL-12, IFN-γ and TNF-α in PBMCs of vaccinated animals as compared to control (un-vaccinated) animals at certain time points was observed. On the other hand, there was a significant increase in mean ± SD percentage of CD8+ T cells after 7 days post challenge (DPC) but, the mean ± SD percentage of CD4+ T-cell population slightly declined at 7 DPC and enhanced after 14 DPC. Significant differences (P<0.05) of CD8+ and CD4+ T cells population was also observed between vaccinated and unvaccinated sheep. The vaccine also significantly (P<0.05) reduced BTV RNA load in PBMCs of vaccinated animals than unvaccinated animals following challenge. There were no significant difference (P>0.05) in cytokine induction, BTV RNA load and CD8+ and CD4+ cell count among BTV-1, 2, 10, 16 and 23 serotype challenges except significant increase in mean ± SD percentage of CD8+ in BTV-2 group. These findings put forwarded that binary ethylenimine inactivated montanide adjuvanted pentavalent bluetongue vaccine has stimulated cell mediated immune response and most importantly reduced the severity of BTV-1, 2, 10, 16 and 23 infections following challenge in respective group.